Algorithmic Genre: Platform Logic, Cultural Hybridity, and the Fluidity of Contemporary Film - Giovani Giovani; Muhammad Ritzky Saibi (MD Research Center, 2026)
The rise of digital media and globalization has fundamentally reshaped film genre theory, shifting it from a rigid classification system to a dynamic, negotiable space of meaning. This study addresses the theoretical gap left by traditional structuralist approaches, which fail to explain the pervasive hybridity and fluidity of genres in contemporary global cinema. Its objective is to analyze how these concepts redefine genre boundaries, examine the influence of streaming platform algorithms on genre formation, and explore how non-Western cinemas employ genre as a tool for cultural expression and resistance. Employing a qualitative literature review methodology with thematic analysis, the research synthesizes key scholarly texts. The findings demonstrate that genre hybridity is not merely an aesthetic choice but is structurally linked to the industrial logics of digital platforms and serves as a vital cultural strategy for identity articulation, particularly in Asian and Latin American films. The study concludes that genre must be reconceptualized as a fluid, hybrid, and discursive practice embedded within broader socio-economic power relations. This reconceptualization provides a crucial framework for understanding film in the digital era, where genre functions simultaneously as an industrial mechanism, a narrative framework, and a site for cultural negotiation.